Determining the Posture and Vibration Frequency that Maximize Pelvic Floor Muscle Activity During Whole-Body Vibration - Lee, Juhyun; Lee, Kyeongjin; Song, Changho (Medical science monitor, 2016)
BACKGROUND The aim of this study was to investigate the electromyogram (EMG) response of pelvic floor muscle (PFM) to whole-body vibration (WBV) while using different body posture and vibration frequencies. MATERIAL AND METHODS Thirteen healthy adults (7 men, 6 women) voluntarily participated in this cross-sectional study in which EMG data from PFM were collected in a total of 12 trials for each subject (4 body postures, 3 vibration frequencies). Pelvic floor EMG activity was recorded using an anal probe. The rating of perceived exertion (RPE) was assessed with a modified Borg scale. RESULTS We found that vibration frequency, body posture, and muscle stimulated had a significant effect on the EMG response. The PFM had high activation at 12 Hz and 26 Hz (p<0.05). PFM activation significantly increased with knee flexion (p<0.05). The RPE significantly increased with increased frequency (p<0.05). CONCLUSIONS The knee flexion angle of 40° at 12 Hz frequency can be readily promoted in improving muscle activation during WBV, and exercise would be performed effectively. Based on the results of the present investigation, sports trainers and physiotherapists may be able to optimize PFM training programs involving WBV.